Peran Guru dalam Membangun Kesadaran Berkonstitusi Melalui Pembelajaran Konstruktif - Lilik, Lilik (Taallum: Jurnal Pendidikan Islam, 2013)
Knowledge, understanding, and the truth of action is important and necessary to be taught and planted from early age. The learners (students) as the subject of learning process are hoped to have constitution concept and able to develop the life pattern culturally. The teacher as the front liner or the lance-point of learning process has a very strategic contribution to develop it. Therefore, the approach used in learning process done by the teacher should combine among knowledge, understanding, and the truth of action. In accordance with those statements above, the model of learning process should reveal any parts of constitution from each subject; describe the facts about constitution problem from every relevant basic competence; study the basic concept of today constitution; and build a certain action/manner of constitution awareness individually or in group. The model of learning process certainly can build the awareness of constitution by applying study of constructive analysis. Generally, the purpose of this writing is to encourage the constitution awareness related to the application of constructive analysis. Moreover, specifically the purpose of this writing is to build the knowledge of constitution, increase the constitution understanding, analyze the truth of constitution action, and encourage the constitution awareness by studying constructive analysis.